2019
DOI: 10.1111/cpf.12611
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning‐based quantification of PET/CT prostate gland uptake: association with overall survival

Abstract: Aim To validate a deep-learning (DL) algorithm for automated quantification of prostate cancer on positron emission tomography/computed tomography (PET/ CT) and explore the potential of PET/CT measurements as prognostic biomarkers. Material and methods Training of the DL-algorithm regarding prostate volume was performed on manually segmented CT images in 100 patients. Validation of the DL-algorithm was carried out in 45 patients with biopsy-proven hormone-na€ ıve prostate cancer. The automated measurements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…Mortensen et al [9] and Polymeri et al [10] used automated segmentation of the prostate. A CNN was trained for automated measurements in [18F]-choline PET/CT scans obtained before radical prostatectomy in patients with newly diagnosed prostate cancer [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mortensen et al [9] and Polymeri et al [10] used automated segmentation of the prostate. A CNN was trained for automated measurements in [18F]-choline PET/CT scans obtained before radical prostatectomy in patients with newly diagnosed prostate cancer [9].…”
Section: Discussionmentioning
confidence: 99%
“…The automated CNN segmentation and the PET measurements provided similar measurements to manually derived measurements. Polymeri et al [10] then used the method to explore the potential of automatic PET/CT measurements as prognostic biomarkers. These authors found that automated PET/CT measurements reflecting total lesion uptake were significantly associated with overall survival, whereas age, prostate-specific antigen, and Gleason score were not.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The vision is that AI methods applied to whole‐body PET/CT scans can provide a single number, the global disease score, to reflect the entire disease burden in the body or part of the body (Høilund‐Carlsen et al., 2019). We have used CNNs to automatically detect and quantify PET tracer activity in the prostate gland and skeleton of patients with PCa (Lindgren Belal et al., 2017; Polymeri et al., 2020). Both methods provided volumetric measurements of tumour burden, which is associated with overall survival.…”
Section: Introductionmentioning
confidence: 99%